Association Between Helicobacter Pylori Infection and Non-alcoholic Fatty Liver Disease, Hepatic Adipose Deposition and Stiffness in Southwest China - Liu, Ying; Li, Dongyu; Liu, Yuping; Shuai, Ping (Frontiers in Medicine, 2021)
Background: Both nonalcoholic fatty liver disease (NAFLD) and Helicobacter pylori (H. pylori) infection have high prevalence worldwide, and the relationship between both remains controversial. We try to investigate whether H. pylori infection is associated with NAFLD and increased liver fat deposition and stiffness in this cross-sectional study. Methods: The physical examination data of 5,665 subjects were obtained from February 2018 to June 2019 in this study. Clinical and biochemical data were collected. NAFLD was diagnosed using abdominal color Doppler ultrasonography. Liver steatosis and stiffness were understood by two parameters of transient elastography (TE): fat attenuation parameter (FAP) and liver stiffness measurement (LSM). H. pylori infection was determined using the 13C urea breath tests. Results: The total prevalence of NAFLD and H. pylori infection was 30.2 and 37.0%, respectively. In men, the prevalence of NAFLD and the levels of FAP and LSM in H. pylori-positive group were significantly higher than H. pylori-negative group (all p < 0.01), but no significant difference was found in women. In men, the infection rate of H. pylori in NAFLD group and LSM ≥ 7.4 kPa group was significantly higher than control group. Multivariate logistic regression analysis revealed that H. pylori infection was not independently associated with NAFLD and FAP ≥ 240 dB/m. However, H. pylori infection was associated with LSM ≥ 7.4 kPa in men. Conclusions: Our study suggests that H. pylori infection is not significantly associated with NAFLD and elevated liver steatosis, whereas it may be the risk factor of elevated liver stiffness in men.